Compensatory financing of energy saving projects in the development of «Smart City» - Tkachenko, V.V.; Klymchuk, M.M.; Klochko , A.A. (Ways to Improve Construction Efficiency, 2020)
The article studies the financial compensation technology Tax Increment Financing (TIF) and offers suggestions on the prospects for attracting investment in energy conservation projects. Compensatory financing for energy conservation projects will enable them to make effective management decisions related to finding sources of funding, building their rational structure, and to share risks among project stakeholders; to protect other assets from default and increase the level of financial and credit obligations of project owners; to promote the increase of the financial leverage ratio, which will lead to an increase in the profitability of joint-stock capital and a decrease in its value as a part of total capital. The essence of TIF is to ensure that investor expenses are reimbursed through special funds, which are filled by tax revenues from the revenues of infrastructure facilities created and put into operation. The basis of this mechanism is a redevelopment, which is used to finance the investor, who invests in construction and reimburses his expenses from the special fund, where the taxes paid by the owners of new consolidated objects are accumulated. Such a scheme for financing investment projects uses the effect of increasing taxes as a result of the implementation of projects aimed at increasing the value of real estate. Based on the conducted research, the main features of the Smart City concept were singled out, as well as their characteristics, the feature of this compensatory technology, which is the locality of the financing object, was identified. Therefore, it is proposed to implement this approach within the framework of the Smart City concept, since it promotes not only the use of modern information platforms of the city's development, but also the principles of sustainable development, including the implementation of energy-saving measures.